Genetic Improvement of Grapevine: Tailoring Grape Varieties for The Third Millennium - A Review - Vivier, M.A.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2019)
The remarkable propagative aptitute of grapevine is one of the key factors contributing to its success as a cultivated species and to the spread of the domesticated grapevine, establishing it as one of the most important fruit species worldwide. Today there are some 8 million hectares of vineyards across the world. It is therefore titting that the successful implementation of the powerful technology of gene manipulation in grapevine is to a large extent reliant on this regenerative ability. Currently, several varieties of grapevines have been successfully genetically transformed, largely by employing somatic embryogenesis to generate highly regenerative target material. Especially attractive in the wine industry is the possibility of improving grapevine varieties by the addition of genes that confer useful traits, such as resistances against biotic and abiotic factors and manipulation of certain metabolic functions. In principle, gene transfer technology allows for the directed manipulation of a specific trait without altering the characteristic nature of the cultivar, permitting the improvement of the traditional cultivars while maintaining their established varietal characteristics. For the most part, targeted traits currently include disease resistance and improved berry quality. The promise of this technology is threatened by worldwide resistance to genetically modified organisms, and in the wine industry by complications surrounding the property rights and naming of transgenic vines. If it is not possible to maintain the varietal name when a transgenic vine has the same properties as the original well known variety, the significant advantages of gene technology over traditional breeding programmes are to a large extent lost. If these and other complications can be overcome, the integration of this powerful technology with traditional breeding programmes, and with other initiatives such as the study of the grapevine genome, will ensure a new era in the cultivation of this ancient species.